2015
DOI: 10.1121/1.4915483
|View full text |Cite
|
Sign up to set email alerts
|

Passive estimation of internal temperatures making use of broadband ultrasound radiated by the body

Abstract: The internal temperatures of plasticine models and the human forearm in vivo were determined, based on remote measurements of their intrinsic ultrasonic radiation. For passive detection of the thermal ultrasonic radiation an acoustic radiometer was developed, based on a broadband 0.8-3.3 MHz disk-shaped ultrasonic detector with an 8 mm aperture. To reconstruct temperature profiles using the experimentally measured spectra of thermal acoustic radiation a priori information was used regarding the temperature dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…This method allows distinguishing weak noise signals, which include thermal acoustic radiation, against the background of the receiver's natural noise. Detailed analysis of the modulation AT based on the results of [3][4][5][6] showed that the minimum detected temperature difference is much worse than the maximum allowable one calculated theoretically. In addition to this drawback, such an AT has limited application due to the need for a priori knowledge of frequency-dependent absorption coefficients and measurements at two frequencies.…”
Section: Literature Review and Problem Statementmentioning
confidence: 82%
“…This method allows distinguishing weak noise signals, which include thermal acoustic radiation, against the background of the receiver's natural noise. Detailed analysis of the modulation AT based on the results of [3][4][5][6] showed that the minimum detected temperature difference is much worse than the maximum allowable one calculated theoretically. In addition to this drawback, such an AT has limited application due to the need for a priori knowledge of frequency-dependent absorption coefficients and measurements at two frequencies.…”
Section: Literature Review and Problem Statementmentioning
confidence: 82%
“…It is shown that the calculated ratios of the first method are simpler for the analysis and calculation of amplitude-frequency piezoelectric emitters for therapeutic devices. The calculated ratios of the second method are simpler when analyzing and calculating piezoelectric receivers, which may be relevant in such areas of application as passive acoustic diagnostic methods: measurement of the deep temperature of the human body with its acoustic thermal radiation [8]. In the case of PTs operating in the combined mode, as in an ultrasonic diagnostic echoscope, the electromechanical quadrupole method can be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…In [40], the authors reconstruct the temperature profile of forearm and plasticine object using broadband acoustic thermometers. The average error is about 0.5K in plasticine object.…”
Section: ∝ 2 (15)mentioning
confidence: 99%